Issues of development of local government system in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
In this article are considered questions of regulation of system of local government in the Republic of Kazakhstan and their developments are considered. In article it is given definitions of system of local government, is analyzed extent of regulation of system of local government in the constitutional legislation of RK, is considered the constitutional fixing of a form of implementation by the population of local government. Forms of direct will of citizens can be various. Usually concern to them local elections, a local referendum, meetings or descents of citizens, a response, a popular law-making initiative, etc. If to open a condition of regulation of system of local government, i.e. to open forms of implementation of local government directly the population under the law 2001 year of «About local public administration and self-government in the Republic of Kazakhstan», only descents of local community and meeting of local community are fixed in the law.Key words: direct democracy, local government, local self-government, municipal authorities, local government system, local elections, local referendum, recall, national law-making initiative, local government bodies.